How and Why Does Immigration Affect Crime? Evidence from Malaysia - Ozden, Caglar (Published by Oxford University Press on behalf of the World Bank, 2019)
The perception that immigration fuels crime is an important source of anti-immigrant sentiment. Using Malaysian data for 2003-10, this paper provides estimates of the overall impact of economic immigration on crime, and evidence on different socio-economic mechanisms underpinning this relationship. The IV estimates suggest that immigration decreases crime rates, with an elasticity of around −0.97 for property and -1.8 violent crimes. Three-quarters of the negative causal relationship between immigration and property crime rates can be explained by the impact of immigration on the underlying economic environment faced by natives. The reduction in violent crime rates is less readily explained by these factors.